2022
DOI: 10.3390/biology11060817
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cannabidiol (CBD) in Cancer Treatment: A Review

Abstract: Cannabis sativa L. (Cannabis) and its bioactive compounds, including cannabinoids and non-cannabinoids, have been extensively studied for their biological effects in recent decades. Cannabidiol (CBD), a major non-intoxicating cannabinoid in Cannabis, has emerged as a promising intervention for cancer research. The purpose of this review is to provide insights into the relationship between CBD and cancer based on recent research findings. The anticancer effects of CBD are mainly mediated via its interaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 75 publications
1
33
0
1
Order By: Relevance
“…Interest in the use of CBD to treat cancer is currently high among researchers and clinicians, as indicated by the large number of recently published articles. Several recent reviews of the topic have examined relevant aspects, including the biochemical, pharmacological, and molecular mechanisms of CBD activity in cells [ 4 , 23 ]; CBD’s mechanism-of-action in cell and mouse models of cancer treatment [ 105 , 106 ]; and its clinical use to manage cancer symptoms [ 107 , 108 ]. We have aimed to synthesize this information and identify unmet needs in the field (standard dosing and true randomization, comparison between pure CBD and CBD+THC formulations, and impact of drug combinations on CBD efficacy), which could serve as the focus for future research and, thus, hasten the clinical translation of CBD.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the use of CBD to treat cancer is currently high among researchers and clinicians, as indicated by the large number of recently published articles. Several recent reviews of the topic have examined relevant aspects, including the biochemical, pharmacological, and molecular mechanisms of CBD activity in cells [ 4 , 23 ]; CBD’s mechanism-of-action in cell and mouse models of cancer treatment [ 105 , 106 ]; and its clinical use to manage cancer symptoms [ 107 , 108 ]. We have aimed to synthesize this information and identify unmet needs in the field (standard dosing and true randomization, comparison between pure CBD and CBD+THC formulations, and impact of drug combinations on CBD efficacy), which could serve as the focus for future research and, thus, hasten the clinical translation of CBD.…”
Section: Discussionmentioning
confidence: 99%
“…Our work is contextualized in the discussion that is taking place in the scientific community on the safety and efficacy of the use of derivatives of Cannabis sativa in patients with cancer, in particular of cannabidiol, the most concentrated molecule in Cannabis devoid of psychotropic effects. Many research papers describe the antiproliferative effect exerted by cannabidiol on 2D and 3D preclinical cell models of cancer and also try to address the molecular mechanistic aspects of these effects [26,[30][31][32]. In this context, we proposed to investigate the effect of CBD, alone and in co-treatment with conventional chemotherapeutic agents, on a cellular model of triple-negative breast cancer (MDA-MB-231 cell line), which is not responsive to the targeted therapies currently clinically available.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the HCT116 cell line bears mutations in the KRAS oncogene, while no mutations are reported for this gene in the HT29 cells. Although not dissected out in this study in detail, recent reports in the literature point to the importance of having a wild-type p53 status for the occurrence of a curcumin-dependent induction of apoptosis in breast and neuroblastoma cancer models (Heider et al, 2022), (Wang et al, 2022). Likewise, the detailed study by Raup-Konsavage et al (2018) showed that among the 370 different cannabinoid compounds they tested on distinct molecular subtypes of CRC cell lines (SW480, SW620, HT-29, DLD-1, HCT-116, LS-174T, RKO), the extent of the therapeutic response was further influenced by the oncogenic Last but not least, potential direct interaction of CBD, CBG and curcumin/piperine with proteins of interest investigated in this study at the transcriptional level can be involved in eliciting differential therapeutic response in the two in vitro models of CRC.…”
Section: Effect Of Cannabinoid Compounds Together With Curcumin and P...mentioning
confidence: 99%